1994
DOI: 10.1007/bf00114202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rodent community during recovery from fire: relevance to conservation

Abstract: Fire is a common disturbance in the Mediterranean ecosystem. A fire that broke out in the eastern Mediterranean pine forest on Mount Carmel in September 1989 destroyed thousands of hectares of natural forest. We carded out a comparative study of rodent recovery after fire under three different management regimes in order to establish the best treatment for recovery. Rodents were used as 'bio-indicators', because of their limited home range, to assess the best management practice to be used in the recovery of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…However, in this study area the incidence of fire was very frequent which could have severe adverse effects on small mammal populations. In previous studies, fire was shown to lower the species diversity due to destruction of vast areas of their habitat and food resources, which could also lead to changes in the behavior (Haim and Izhaki, 1994;Clausnitzer, 2003). Similar effects might have contributed to the small mammal fauna of CCNP.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study area the incidence of fire was very frequent which could have severe adverse effects on small mammal populations. In previous studies, fire was shown to lower the species diversity due to destruction of vast areas of their habitat and food resources, which could also lead to changes in the behavior (Haim and Izhaki, 1994;Clausnitzer, 2003). Similar effects might have contributed to the small mammal fauna of CCNP.…”
Section: Discussionmentioning
confidence: 99%
“…Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 10:13 PM Studies on post-fire recolonization by small mammals are relatively numerous in the Mediterranean Region (Arrizabalaga et al, 1993;Fons et al, 1988;Fuentes et al, 1998;Haim & Izhaki, 1994;Prodon et al, 1987;Torre & Díaz, 2004), but studies on post-fire recolonization of the small mammal helminths are relatively scarce (Feliu et al, 1993;Fuentes et al, 1998Fuentes et al, , 2005Fuentes et al, , 2007Torres et al, 1992). Parasites can be considered as biological tags for post-fire recolonization studies owing the close relationships with their hosts .…”
Section: Discussionmentioning
confidence: 99%
“…During the dry season, the vegetation in the Mediterranean ecosystem is expected to have an increased particle (or osmotic) concentration owing to higher evaporation of water (Main, 1986;Haim & Izhaki, 1994;Grammatikipoulos, 1999). Therefore, animals such as A. cahirinus, which may depend upon vegetation as a water source, face an increasing osmotic load as the dry season progresses.…”
Section: Introductionmentioning
confidence: 99%